2021
DOI: 10.3390/w13111534
|View full text |Cite
|
Sign up to set email alerts
|

Status of Endemic Freshwater Fish Fauna Inhabiting Major Lakes of Turkey under the Threats of Climate Change and Anthropogenic Disturbances: A Review

Abstract: Due to its peculiar geographical position and its environmental heterogeneity, Turkey represents an important biodiversity hotspot for freshwater fish fauna. Unfortunately, native fish communities of Turkey, mainly from lentic ecosystems, have been massively altered in the past decades. Furthermore, these species, especially the endemic species, are now threatened by several human activities in addition to the global issue of climatic changes. The aim of this paper is to provide an updated review on the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Also, Doney et al (2012) went on to say that temperature has an effect on freshwater ecosystems and food availability, so it can be stated here that the change in climate over the seasons would force fish to adapt their diets to the environmental conditions, and it influences the change in the morphometric parameters. In their recent study, Giannetto & Innal (2021) showed that the decreasing water level and the climatic drought were found to be the threats that affect the fish communities the most.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Doney et al (2012) went on to say that temperature has an effect on freshwater ecosystems and food availability, so it can be stated here that the change in climate over the seasons would force fish to adapt their diets to the environmental conditions, and it influences the change in the morphometric parameters. In their recent study, Giannetto & Innal (2021) showed that the decreasing water level and the climatic drought were found to be the threats that affect the fish communities the most.…”
Section: Discussionmentioning
confidence: 99%
“…They pose a risk, especially in terms of endemic species persistence (Margaritora et al, 2001;Buttermore et al, 2011). This threat is signally higher, especially for "microendemic" (which have a very limited distribution) fish species (Giannetto and Innal, 2021). In Turkey, many of the endemic fish species have microendemic status, which makes their survival more at risk.…”
Section: Introductionmentioning
confidence: 99%
“…During COVID-19 and lockdown periods, few studies performed relating to public aquariums. Giannetto & Innal (2021) did one of these studies. In the study, status of endemic freshwater fish fauna inhabiting major Lakes of Turkey investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, status of endemic freshwater fish fauna inhabiting major Lakes of Turkey investigated. The authors (Giannetto & Innal, 2021) reported 62 endemic fish species. Climate change and anthropogenic disturbances were found to be the threats that most affect the fish communities of the considered Turkish Lakes.…”
Section: Introductionmentioning
confidence: 99%